Maternal health concerns - Jamani, Nurjasmine Aida (2014)
Mother need to get enough nutrition when she is breastfeeding. The mother need to eats in sufficient amounts, to get all proteins, vitamin and minerals that she needs. Milk is partly produce from fat stores during pregnancy and partly from the food that she eats.